2017
DOI: 10.1371/journal.pone.0178815
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and genetic correlation between GERD symptoms severity, metabolic syndrome, and inflammation markers in families living in Mexico City

Abstract: ObjectiveThe aim of this study was to estimate the heritability (h2) and genetic correlation (ρG) between GERD symptoms severity, metabolic syndrome components, and inflammation markers in Mexican families.MethodsCross-sectional study which included 32 extended families resident in Mexico City. GERD symptoms severity was assessed by the ReQuest in Practice questionnaire. Heritability and genetic correlation were determined using the Sequential Oligogenic Linkage Analysis Routines software.Results585 subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 37 publications
0
11
0
10
Order By: Relevance
“…the proportion of phenotypic variance attributed to additive fetal genetic variance 15 , (2) environmental variances (shared by both twins in a pair and unique to each co-twin), and (3) genetic correlation between fetal growth measures, which measures the proportion of covariance of two traits explained by additive fetal genetics using the Sequential Oligogenic Linkage Analysis Routines (SOLAR) software version 7.2.5 62 ( http://solar-eclipse-genetics.org/ ). SOLAR implements a structural equation modeling approach to estimate additive genetic heritability, shared and unique environmental contributions and the best-fitting variance component models using the maximum-likelihood method 63 65 .…”
Section: Methodsmentioning
confidence: 99%
“…the proportion of phenotypic variance attributed to additive fetal genetic variance 15 , (2) environmental variances (shared by both twins in a pair and unique to each co-twin), and (3) genetic correlation between fetal growth measures, which measures the proportion of covariance of two traits explained by additive fetal genetics using the Sequential Oligogenic Linkage Analysis Routines (SOLAR) software version 7.2.5 62 ( http://solar-eclipse-genetics.org/ ). SOLAR implements a structural equation modeling approach to estimate additive genetic heritability, shared and unique environmental contributions and the best-fitting variance component models using the maximum-likelihood method 63 65 .…”
Section: Methodsmentioning
confidence: 99%
“…Gastro-esophageal reflux disease (GERD) is defined as a condition that develops when reflux of stomach contents causes troublesome symptoms and/or complications [ 1 ]. Apart from the well- recognized complications like erosive esophagitis and Barrett’s esophagus, GERD has been linked to sleep disorders, metabolic syndrome, and coronary artery disease [ 2 4 ]. GERD affects almost all age groups starting from infancy.…”
Section: Introductionmentioning
confidence: 99%
“…A year later, Mohammed et al[ 38 ] examined 4480 pairs of twins, which inferred 30% heritability of GERD, while the same symptoms in MZ outnumbered the DZ ones. Another study of 585 individuals concerning 32 families living in Mexico revealed an association between the severity of GERD symptoms, metabolic syndrome components and inflammatory markers due to common genetic back round[ 39 ].…”
Section: Genetic Risk Factorsmentioning
confidence: 99%